Evaluation of potential immunogenicity differences between Pandemrix™ and Arepanrix™. Issue 9 (1st September 2016) - Canelle, Quentin; Dewé, Walthère; Innis, Bruce L.; van der Most, Robbert
ABSTRACT: In retrospective observational studies, an increased relative risk of incident narcolepsy was observed in some European countries among recipients of the AS03-adjuvanted, A(H1N1)pdm09, inactivated, detergent-split virion vaccine Pandemrix ™ manufactured in Dresden, Germany (D-Pan H1N1). A similar increased risk was not observed in a retrospective population-based study in individuals in Quebec province, Canada, who received Aprepanrix ™, a Quebec-manufactured AS03-adjuvanted A(H1N1)pdm09 inactivated, detergent-split virion vaccine (Q-Pan H1N1). Antibody responses in D-Pan versus Q-Pan vaccinees (adults/children) measured as hemagglutination inhibition (HI) titers 21 d post-vaccination were found to be equivalent (NCT01161160). The current post-hoc analysis was conducted to determine whether antibody avidity differed following immunization with the 2 vaccines. Using surface plasmon resonance, we evaluated the capacity of serum specimens (drawn from the comparative immunogenicity trial) from a subset of subjects aged 3–9 y who received either D-Pan or Q-Pan (N = 28/group), to bind to recombinant A(H1N1)pdm09 hemagglutinin. IgG antibodies were purified from Day 21 sera. Binding was assessed by end association level; dissociation by retention of antigen-antibody complexes at the end of the dissociation phase, and kd . Inter-run variability for the control monoclonal antibody, association levels and dissociation levels was low (CVs 1.3%, 7.8% and 1.4%, respectively); non-specific binding was negligible. High avidity and slow dissociation was observed for both groups (kd ≤ 10 −4 /s; geometric mean [IQR] association and dissociation levels for D-Pan/Q-Pan: 15.4 RU [13.4–17.7]/12.4 RU [10.8–14.3] and 94.5% [92.5–96.5]/95.5% [93.5–97.6], respectively). Association, but not dissociation levels correlated with HI titers. No significant differences in avidity parameters were observed between D-Pan and Q-Pan sera.